2013
DOI: 10.1186/1471-2458-13-40
|View full text |Cite
|
Sign up to set email alerts
|

Level of awareness of mammography among women attending outpatient clinics in a teaching hospital in Ibadan, South-West Nigeria

Abstract: BackgroundMammography has been used in developed countries with considerable success but very little is known about this imaging modality in low resource settings. This study examined the level of awareness of mammography and determined factors influencing the level of awareness.MethodsWe conducted a hospital based cross sectional study to investigate the level of awareness of mammography among 818 randomly selected women attending the General Outpatient clinics (GOP) of the University College Hospital (UCH), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 18 publications
2
23
2
Order By: Relevance
“…In Nigeria, the awareness among women regarding mammography was even poorer at 5% (Obajimi et al, 2013) Although awareness of breast cancer is high in Malaysia, this did not correspond well with awareness of available screening measures. When awareness of mammography screening is low, it is not surprising that the prevalence of mammography screening uptake will be low at 13.2% as found in our study.…”
Section: Discussionmentioning
confidence: 89%
“…In Nigeria, the awareness among women regarding mammography was even poorer at 5% (Obajimi et al, 2013) Although awareness of breast cancer is high in Malaysia, this did not correspond well with awareness of available screening measures. When awareness of mammography screening is low, it is not surprising that the prevalence of mammography screening uptake will be low at 13.2% as found in our study.…”
Section: Discussionmentioning
confidence: 89%
“…This is in line with findings from other studies. [11,17] The multivariate analysis showed that women aged 40 years and above were more likely to be aware of mammography in this study. This may be linked to the fact that this group of women are also the ones eligible for routine mammographic screening.…”
Section: Discussionmentioning
confidence: 56%
“…Osime15 reported another study with 35% awareness of mammography among civil servants. 14 Akinola reported an awareness level of 40.5% among a hospital sample. In our study majority (65%) of the women had undergone only secondary education.…”
Section: Discussionmentioning
confidence: 94%